2017
DOI: 10.1099/jgv.0.000893
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of molecular and genetic evolution, antigenicity and virulence properties during the persistence of the infectious bronchitis virus in broiler breeders

Abstract: The infectious bronchitis virus (IBV) causes a highly contagious disease [infectious bronchitis (IB)] that results in substantial economic losses to the poultry industry worldwide. We conducted a molecular and phylogenetic analysis of the S1 gene of Brazilian (BR) IBV isolates from a routinely vaccinated commercial flock of broiler breeders, obtained from clinical IB episodes that occurred in 24-, 46- and 62-week-old chickens. We also characterized the antigenicity, pathogenesis, tissue tropism and spreading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Although not longitudinally sampled, MERS-CoV was detected at frequencies of Ͼ40% in several groups of dromedary camels, similarly indicative of persistence (47) despite its more frequent clearance in infected humans (48). Other coronaviruses showing long-term persistence include mouse hepatitis virus, feline calicivirus (49), and infectious bronchitis virus in birds (50,51). Pigs are infected with a range of different coronaviruses of variable propensities to establish persistent infections (52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Although not longitudinally sampled, MERS-CoV was detected at frequencies of Ͼ40% in several groups of dromedary camels, similarly indicative of persistence (47) despite its more frequent clearance in infected humans (48). Other coronaviruses showing long-term persistence include mouse hepatitis virus, feline calicivirus (49), and infectious bronchitis virus in birds (50,51). Pigs are infected with a range of different coronaviruses of variable propensities to establish persistent infections (52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, protectotype analysis of some nephropathogenic BR-I IBV strains demonstrated that Massachusetts live attenuated vaccines conferred only partial protection to tracheal and kidney tissues [12, 14], although the combination of Massachusetts and 793B live attenuated vaccines improved protection against these BR-I nephropathogenic strains [12]. Additionally, virus neutralization tests (VNT) showed that some BR-I genotype strains do not belong to the Massachusetts serotype [5, 34].…”
mentioning
confidence: 99%
“…The Mass IBV strain can persist in the cecal tonsils, spleen and kidney for about a month [ 78 ]. Although the period of IBV persistence is influenced by the age at infection [ 42 ], the length of persistence does not depend on the systemic anti-IBV antibody concentration [ 4 ]. The implications of IBV persistence in chickens are twofold.…”
Section: Ibv Persistencementioning
confidence: 99%
“…The implications of IBV persistence in chickens are twofold. First, persistently infected chickens are a source of infection for naïve chickens [ 4 ]. Second, persistent IBV infection promotes viral evolution [ 4 ].…”
Section: Ibv Persistencementioning
confidence: 99%
See 1 more Smart Citation